Gestational stress disrupts dopamine and oxytocin signaling in the postpartum reward system of rats: implications for mood, motivation and mothering - Achikam Haim; Christopher Albin-Brooks; Holly Brothers; Michaela Breach; Benedetta Leuner (Scientific Reports)
Abstract Postpartum depression (PPD) affects up to 20% of new mothers and has adverse consequences for the well-being of both mother and child. Exposure to stress during pregnancy as well as dysregulation in the mesolimbic dopamine (DA) reward system and its upstream modulator oxytocin (OT) have been independently linked to PPD. However, no studies have directly examined DA or OT signaling in the postpartum brain after gestational stress. Here we employed a chronic variable stress procedure during pregnancy and evaluated behavioral measures of mood and reward along with assessments of DA and OT signaling in postpartum rats. Our results show that gestational stress induced postpartum depressive-like and anxiety-like behavior in addition to producing reward-related deficits including anhedonia, impaired maternal care, and reduced maternal motivation. Consistent with a hypodopaminergic state, histological analysis revealed reduced expression of tyrosine hydroxylase in the NAc shell and core as well as reduced expression of the dopamine transporter and dopamine D2 receptor in the NAc shell of postpartum females exposed to gestational stress. A reduction in accumbal DA content as determined by liquid chromatography-mass spectrometry was also observed in gestationally-stressed dams. Lastly, we assessed mRNA expression of OT and OT receptors (OTR) and found that gestational stress increased OT expression in the hypothalamus but reduced OTR expression in the postpartum ventral tegmental area (VTA), a target of hypothalamic OT neurons. In the VTA, a reduction in OT-immunoreactive fibers following gestational stress was also seen. Taken together, these data demonstrate that the DA and OT systems within the postpartum reward circuit are sensitive to gestational stress and suggest that mood and maternal disruptions in PPD may arise from dysfunctional oxytocinergic regulation of the dopaminergic reward system.